A tri-band, 2-RX MIMO, 1-TX TD-LTE CMOS transceiver. Issue 1 (January 2015) - Huang, Mo; Chen, Dihu; Guo, Jianping; Xu, Ken; Ye, Hui; Liang, Xiaofeng; Dagher, Elias H.; Xu, Bin; Masenten, Wesley K.
Abstract In this work, a tri-band (Band 39: 1880–1920 MHz, Band 40: 2300–2400 MHz, and Band 38: 2570–2620 MHz), 2-receiver (RX) multiple-in-multiple-out (MIMO), 1-transmitter (TX) TD-LTE (Time Division Long Term Evolution) CMOS transceiver is presented and fabricated in 0.13-μm CMOS technology. The continuous-time delta–sigma A/D converters (CT ΔΣ ADCs) are directly coupled to the RX front-end outputs to achieve low power. With proper gain allocation and a novel carrier leakage calibration, the TX section ensures at least –40 dBc carrier leakage suppression over 86-dB gain range. The transceiver dissipates maximum 171 mW at 2-RX MIMO mode and 183 mW at 1-TX maximum gain mode. To the best of our knowledge, this is the first research paper on fully integrated commercial TD-LTE transceiver.